2017
DOI: 10.3390/ijms19010051
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Roles of TWIK-1 Heterodimerization in the Brain

Abstract: Two-pore domain K+ (K2P) channels play essential roles in regulating resting membrane potential and cellular excitability. Although TWIK-1 (TWIK—tandem of pore domains in a weak inward rectifying K+ channel) was the first identified member of the K2P channel family, it is only in recent years that the physiological roles of TWIK-1 have been studied in depth. A series of reports suggest that TWIK-1 may underlie diverse functions, such as intrinsic excitability of neurons, astrocytic passive conductance, and ast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…In mHb ChNs, there are high expressions of at least two types of K 2P channels, TASK-3 and TWIK-1 45 . The two K 2P channels may interact to form heteromeric channels as well as homomeric ones 58, 59 , which may exhibit unique pharmacology. Thus, low expressions of histamine receptors as well as K 2P channel compositions may render mHb ChNs’ pace-making activity insensitive to histamine.…”
Section: Discussionmentioning
confidence: 99%
“…In mHb ChNs, there are high expressions of at least two types of K 2P channels, TASK-3 and TWIK-1 45 . The two K 2P channels may interact to form heteromeric channels as well as homomeric ones 58, 59 , which may exhibit unique pharmacology. Thus, low expressions of histamine receptors as well as K 2P channel compositions may render mHb ChNs’ pace-making activity insensitive to histamine.…”
Section: Discussionmentioning
confidence: 99%
“…Deficiency of TWIK-1 induced with specific short hairpin RNA (shRNA) results in increased RMP, which increases the excitability of hippocampal dentate gyrus (DG) granule neurons [7,8]. Additionally, TWIK-1 is a key component of astrocytic passive conductance, which is important for potassium buffering [9][10][11][12]. Therefore, these previous studies strongly suggest the important physiological roles of TWIK-1 channels in various tissues including the brain.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, TWIK-1 knockout mice show defects in phosphate transport in the proximal tubule and water transport in the medullary collecting duct of the kidney, as well as hyperpolarization in the resting membrane potential of pancreatic cells [5,6]. In addition, we recently reported that TWIK-1 contributes to maintaining proper neuronal excitability and astrocytic passive conductance in the mouse hippocampus [7][8][9][10][11]. Deficiency of TWIK-1 induced with specific short hairpin RNA (shRNA) results in increased RMP, which increases the excitability of hippocampal dentate gyrus (DG) granule neurons [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…PD-1 is expressed on activated CD4 + and CD8 + T-cells and interaction of PD-1 with its ligands results in the suppression of T-cell sensitivity to antigenic stimulation 23 , 24 . Tim-3 is mainly present on Th1 (helper T-cell 1) and Tc1 (cytotoxic T-cell 1) subsets, but it is also expressed on innate immune cells such as dendritic cells (DCs), natural killer (NK) cells, and monocytes 25 .…”
Section: Introductionmentioning
confidence: 99%
“…In chronic HIV, HBV, and HCV infection, elevated PD-1 and/or Tim-3 expression characterize subpopulations of both total and virus-specific exhausted T-cells 9 , 17 , 28 , 29 . Functional exhaustion can be reversed by blocking of interactions of iRs with their ligands 23 , 27 , 30 32 , but exclusive blockade of the PD-1 pathway with specific monoclonal antibodies does not fully restore cell functionality. McMahan et al 17 showed that blocking of either the PD-1 or Tim-3 pathway enhances proliferation of HCV-specific CD8 + T-cells in vitro, whereas cytotoxicity against a hepatocyte cell line expressing cognate HCV epitopes was increased exclusively by Tim-3 blocking.…”
Section: Introductionmentioning
confidence: 99%